Trauma Discourse in Christopher Robin Movie - Fadilatul Nadia; Ansor Putra; Neil Amstrong (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2024)
This research is based on the trauma of someone in a movie, seen in the movie used trauma discourse theory. The objective of this research is to find out how the trauma discourse appeared in Christoper Robin's movie based on Zaumseil and Indradjaja's theory. This research used a descriptive qualitative method. The source of data in this research was taken from the Disney watch page. The researcher found that two elements of trauma discourse seen in two characters are Christoper Robin and Winnie the Pooh in the two aspects such as reasonable fear and worry and culturally specific suffering in terms of the inner and outer realm of trauma discourse. From the several aspects above, the creation of past trauma has an impact on finding out the characteristics of people who experience discourse trauma in their speech both for them and for those around them. This research concludes that someone who has experienced trauma is very influential when he speaks or conveys a message. This can be seen from the language used and the actions taken by the characters in the film Christopher Robin.